The origin of dielectric relaxation behavior in TiO2 based ceramics co-doped with Zn2+, W6+ ions under a N2/O2 sintering atmosphere. Issue 10 (24th February 2023) - Zhou, Lin; Yang, Guoyan; Yang, Dong; Xu, Jinhua; Peng, Zhanhui; Wu, Di; Wei, Lingling; Liang, Pengfei; Chao, Xiaolian; Yang, Zupei
Abstract : We systematically studied the mechanism of dielectric behavior of Zn 2+, W 6+ co-doped TiO2 ceramics under different sintering atmospheres by means of impedance spectra and so on. Abstract : Dense (Zn0.5 W0.5 ) x Ti1− x O2 (ZWTO x ) ceramics were fabricated using a conventional solid state reaction method with sintering under a nitrogen atmosphere (ZWTO x -N2 ) and an oxygen atmosphere (ZWTO x -O2 ), respectively. Colossal permittivity ( ε > 10 4 ) and low loss (tan δ < 0.1) were simultaneously achieved in ZWTO x -N2 ceramics, and two types of dielectric relaxation behaviors observed were interpreted to be due to interface polarization and disassociation between oxygen vacancies and trivalent titanium ions, respectively. The impedance plots suggested that the ZWTO x -N2 ceramics are electrical heterostructures composed of semiconductor and insulator grain boundaries, which proved that the CP performance of ZWTO x -N2 ceramics almost originates from the internal barrier layer capacitance (IBLC) effect. In addition, a series of anomalous dielectric behaviors such as low permittivity and low frequency dispersion were observed for ZWTO x -O2 ceramics; polarization ( P )–electric field ( E ) hysteresis loop curves were obtained for ZWTO x -O2 ceramics, and that impedance plots have shown that the ZWTO x -O2 ceramics display higher insulation resistivity. Density functional theory (DFT) calculations illustrated that the Zn 2+ –W 6+ ion pairs are easy to form in ZWTO x -O2 ceramics, which causes destruction of the local lattice and thus leads to abnormal dielectric behavior. This work will provide a new strategy for defect engineering in TiO2 and other CP materials.